Evaluation of Optical Low Coherence Reflectometry Parameters in Patients with Exfoliation Syndrome - Emrullah Beyazyıldız; Özlem Beyazyıldız; Süleyman Günaydın; Emrah Kan; Mert Şimşek; Pelin Yılmazbaş; Faruk Öztürk (Journal of Ophthalmology)
Purpose. To evaluate optical low coherence reflectometry (OLCR) parameters in patients with exfoliation syndrome (EXS) undergoing cataract surgery. Methods. Forty-seven eyes of 47 patients with EXS (Group 1), and 55 eyes of 55 healthy subjects (Group 2) were included in the study. Anterior chamber depth (ACD), lens thickness (LT), axial length (AL), central corneal thickness (CCT), horizontal corneal length (HCL), and pupil diameter (PD) parameters were measured by OLCR (Lenstar LS 900, Haag-Streit) and compared between groups. Shapiro-Wilk test and Mann Whitney U tests were used for statistical analyses. Results. The mean ACD, HCL, and PD values were significantly lower in EXS group than in healthy subjects (P = 0.01, P = 0.04, and P<0.001, resp.). The mean LT was significantly higher in EXS group than in healthy subjects (P = 0.007). There was no significant difference between groups in means of AXL and CCT. Conclusions. According to OLCR measures, eyes with EXS have shallower ACD, smaller PD, thicker LT, shorter HCL, and no significantly different CCT levels.